PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH, GOOD GOVERNANCE, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN KOTA DENPASAR - I Gede Agus Junyantara; I Putu Deddy Samtika Putra (UNHI Press, 2021)
This study aims to determine the effect of implementing a government internal control system, good governance, the use of information technology on the quality of financial reports in the city of Denpasar. The place for this research was conducted in the Regional Apparatus Organization Unit (OPD) of Denpasar City. The data used are primary data using a questionnaire. The sampling method used in this study was purposive sampling technique. The population in this study amounted to 27 regional apparatus organizations (OPD) in the form of offices and agencies in Denpasar City. In this study using 3 criteria, namely the head of the finance department, treasurer, and financial department employees who have a minimum service period of three years. So the sample in this study amounted to 81 respondents. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that the implementation of the government internal control system has a positive and significant effect on the quality of financial reports for the city of Denpasar, good governance has a positive and significant effect on the quality of financial reports for the city of Denpasar, the use of information technology does not have a significant effect on the quality of financial reports for the city of Denpasar. For the OPD of Denpasar City to improve and implement a government internal control system, Good Governance, the use of information technology in order to create quality financial reports. And for the next researcher, it is expected to add other variables or a different location so that they can be compared with previous studies.